Hubungan Karakteristik dan Pengetahuan yang diukur dengan kuesioner HK-LS (Hyoertension Knawledge-Level Scale) pada Pasien Hipertensi di Puskesmas Banjarmasin - Aryzki, Safti; Faisal, Ahmad; Noval, Noval (Jurnal Farmasi & Sains Indonesia, 2023)
Hypertension or often called high blood pressure is an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg. Hypertension is called the silent killer disease because it often occurs without complaint because it shows no symptoms. Puskesmas is one of the health service facilities in indonesia which aims to increase awareness and ability to live a healthy life for everyone who lives in the work area. To determine the relationship between the characteristics and knowledge of hypertensive patients at the Pekauman Health Center, Banjarmasin City. The method used in the study is a quantitative method with a purposive sampling technique. This research was conducted from December to July 2023 at the Pekauman Health Center in Banjarmasin City with a sample of 96 respondents who met the inclusion and exclusion criteria. The results of the study obtained 96 respondent, the most respondent aged 46-55 years 53 people (55,21), the sex which was mostly female was 75 people (78,13%), the most education was  junior high school education 47 people (43,75%), the most jobs are housewives as many as 75 people (78,12%), the results obtained with the chi-square test based on age characteristics p= 0,002, in gender 0,026, in education 0,000, in jobs 0,036 means p<0,05, so there is a relationship between the characteristics and knowledge of hypertensive patients. Based on the results of research that has been done there is a relationshi